Does caffeine added to carbohydrate provide additional ergogenic benefit for endurance? - Conger, S. A.; Warren, G. L.; Hardy, M. A.; Millard-Stafford, M. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
Carbohydrate (CHO) and caffeine (CAF) both improve endurance performance. Purpose: To determine by systematic literature review coupled with meta-analysis whether CAF ingested with CHO (CHO+CAF) improves endurance performance more than CHO alone. Methods: Databases were searched using the keywords caffeine, endurance, exercise, carbohydrate, and performance. Criteria for inclusion were studies that used human subjects performing an endurance-exercise performance task and included both a CHO and CHO+CAF condition. Effect sizes (ESs) were calculated as the standardized mean difference. Results: Twenty-one studies met the criteria for analysis. ESs for individual studies ranged from -0.08 (trivial effect favoring CHO) to 1.01 (large effect favoring CHO+CAF). The overall ES equaled 0.26 (95% CI 0.15-0.38, p < .001), indicating that CHO+CAF provides a small but significant performance benefit over CHO. ES was not significantly (p > .05) related to CAF dose, exercise duration, or performance-assessment method. To determine whether ES of CHO+CAF vs. CHO was different than CAF compared with water (placebo), a subgroup meta-analysis compared 36 CAF vs. placebo studies against the 21 CHO+CAF vs. CHO studies. The overall ES for the former group of studies (ES = 0.51, 95% CI 0.40-0.61) was nearly 2-fold greater than in CHO+CAF vs. CHO studies (p = .006). Conclusions: CHO+CAF ingestion provides a significant but small effect to improve endurance performance compared with CHO alone. However, the magnitude of the performance benefit that CAF provides is less when added to CHO than when added to placebo.